X-RAYING THE BOUNDS OF THE IGBO APPRENTICESHIP SYSTEM (IAS): IMPLICATIONS FOR ENTREPRENEURSHIP EDUCATION AND JOB CREATION IN EMERGING ECONOMIES - Matthew Agama, Adoga; Cynthia Ohajionu, Uchechi (International Journal of Psychosocial Rehabilitation, 2024)
The overall aim of this study is to provide contextual evidence and deepen understanding of howthe Igbo Apprenticeship System, anchored on the Theory of Experiential Learning (TEL), canenhance the effectiveness of entrepreneurship education and practice in Nigeria and otheremerging economies. The research design/approach adopted in this study is the Model approachfor designing conceptual studies.This approach involves identifying new connections betweenphenomena, building of theoretical propositions that uncover new constructs and/or connectionsbetween constructs, and explaining the reason behind the outcome from a sequence of events.Afunctional and viable entrepreneurial development system with almost a century-long evidenceof job and wealth creation exists to addresscritical macroeconomic issues such as risingunemployment, widespread poverty and economic stagnation. The proposed adapted IASsignificantly reduces rate of startup failures, increases rate of business startups and ultimately,facilitates national economic growth and development. These arguments are not simply based onthe observable evidence of the socioeconomic impact of the IAS among the Igbo ethnic group,but also on grounded theory of learning (Experiential Learning Theory) and emerging evidencesfrom empirical studies in entrepreneurship education and practice